2004
DOI: 10.1002/biof.552210130
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of phorbol ester‐induced COX‐2 expression by some edible African plants

Abstract: Cancer bush (CB, Sutherlandia frutescens), Devil's claw (DEV, Harpagophytum procumbens), Rooibos tea (RT, Aspalathus linearis), and Bambara groundnut (BB, Vignea subterranean) have been used to treat some malignancies and inflammatory disorders in Africa. However, biochemical basis for chemopreventive effects of these medicinal plants remains unclear. An abnormally elevated expression of cyclooxygenase-2 (COX-2) has been implicated in pathogenesis and progression of carcinogenesis. In the present study, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Rooibos and honeybush also possess antioxidant and anti-inflammatory properties that have been implicated in the photoprotective and anti-carcinogenic mechanisms in skin [38][39][40]. The anti-inflammatory activity against cytokine production by quercetin, rutin and luteolin, also present in rooibos, has been shown to involve inhibition of pro-inflammatory cytokine synthesis of via suppression of transcription factors and MAP kinases [31,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rooibos and honeybush also possess antioxidant and anti-inflammatory properties that have been implicated in the photoprotective and anti-carcinogenic mechanisms in skin [38][39][40]. The anti-inflammatory activity against cytokine production by quercetin, rutin and luteolin, also present in rooibos, has been shown to involve inhibition of pro-inflammatory cytokine synthesis of via suppression of transcription factors and MAP kinases [31,46].…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of inflammation by the polyphenolic constituents has been proposed as a key mode of action underlying the protective activity of the extracts. The anti-inflammatory properties of rooibos and honeybush against UVB and PMA-induced COX-2 expression and oedema have been demonstrated and implicated in the anti-tumour activity of the herbal tea extracts in skin [39,40]. However, the modulatory activity of the herbal teas against primary cytokines involved in the early stages of UVB-induced inflammation as well as the effect on cell growth parameters still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro Methanol extract Extract (1, 5, 10 g/ml) inhibited TPA-induced COX-2 expression in human epithelial (MCF10A) cells Na et al (2004) Inhibited TPA-induced COX-2 expression through suppression of DNA binding of NF-B Fermented…”
Section: In Vivomentioning
confidence: 99%
“…Interestingly, a harpagoside-free extract also markedly inhibited inducible NO synthase expression and in contrast to pure harpagoside exerted strong antioxidative activity (Kaszkin et al, 2004). Recently, it was shown that a methanolic extract of devil's claw inhibited TPA (12-Otetradecanoylphorbol-13-acetate)-induced COX-2 expression in human breast epithelial cells and in mouse skin in vivo by inhibiting DNA-binding of NF-B activated by TPA (Na et al, 2004). Topical application of the extract also inhibited TPA-induced activation of activator protein-1 and attenuated the expression of its key component c-Fos (Kundu et al, 2005).…”
Section: Introductionmentioning
confidence: 96%